2021
DOI: 10.1002/pat.5422
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(styrene‐co‐allylamine)‐b‐poly(2‐(dimethylamino)ethyl methacrylate) graft copolymers via “grafting from” atom transfer radical polymerization and their self‐assembly in aqueous media

Abstract: In this work, we report a new synthetic scheme for synthesis of graft copolymers. At first, poly(styrene-co-acrylonitrile) copolymers with different molecular weights were synthesized via atom transfer radical polymerization (ATRP). Then, lithium aluminum hydride was used as reducing catalyst of nitrile groups to obtain poly(styrene-coallylamine) copolymers. Amine groups of poly(styrene-co-allylamine) copolymers were reacted to 2-bromo-2-methylpropionyl bromide (BiBB) to yield poly(styrene-co-N-allyl-2-bromo-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Numerous references of PEGMA-based copolymers have been reported that received immense attention in the recent past. [120][121][122][123][124][125][126][127][128]…”
Section: Other Water-soluble Acrylate Blocksmentioning
confidence: 99%
“…Numerous references of PEGMA-based copolymers have been reported that received immense attention in the recent past. [120][121][122][123][124][125][126][127][128]…”
Section: Other Water-soluble Acrylate Blocksmentioning
confidence: 99%